Incidence and risk factor analysis of complications after sentinel node biopsy for penile cancer. (17th March 2022) - Wever, Lieke; de Vries, Hielke M.; Dell'Oglio, Paolo; van der Poel, Henk G.; Donswijk, Maarten L.; Sikorska, Karolina; van Leeuwen, Fijs W.B.; Horenblas, Simon; Brouwer, Oscar R.
Abstract : Objective: To determine the incidence and types of complications after dynamic sentinel node biopsy (DSNB) in patients with penile cancer (PeCa) and identify risk factors for the occurrence of postoperative complications. Patients and Methods: We evaluated 644 patients with PeCa (1284 DSNB procedures) with at least one clinically node negative (cN0) groin who underwent DSNB between 2011 and 2020 at a single high‐volume centre. The 30‐ and 30–90‐day postoperative complications were collected according to the modified Clavien–Dindo classification and the standardised methodology proposed by the European Association of Urology panel. Uni‐ and multivariable generalised linear mixed models were used to identify risk factors for the occurrence of complications per groin. Results: A 30‐day postoperative complication occurred in 14% of groins ( n = 186), of which 94% were mild to moderate. Wound infection and lymphocele formation were most common. A 30–90‐day postoperative complication occurred in 3.4% of the groins, all of which were mild or moderate (Grade I–II). The number of removed lymph nodes (LNs) per groin was the main independent predictor for any 30‐day complications and Grade ≥II complications (odds ratio 1.40; P < 0.001). There was an increase in the probability of postoperative complications with the number of LNs removed after accounting for all confounders. Conclusions: Despite being less morbid than (modified) inguinal LN dissection, DSNB is still associated with a considerable risk of postoperative mild‐to‐moderate complications. This risk increases with increasing number of LNs removed. Further procedural refinement aimed at removing the true sentinel node(s) only, may help further reduce the morbidity of surgical staging in PeCa.